Family planning practices of women working in the Cambodian garment industry: a qualitative study - Chisato Masuda; Elisa Oreglia; Sokhey Ly; Megan McLaren; Caroline Free; Camille Tijamo; Amra Ou; Michelle Helena van Velthoven; Amy Williamson; Chris Smith (BMC, 2020)
Abstract Background Women working in Cambodian garment factories have unmet needs for family planning (contraception and safe abortion) services, because of their background and living conditions. This study describes their experiences regarding abortion and contraception as part of a larger project to develop an intervention to support comprehensive post-abortion care. Methods We conducted semi-structured interviews with women seeking abortion services at private health facilities. In addition, we interviewed the private providers of abortion and contraception services surrounding garment factories. Interviews lasted up to 60 min and were conducted in Khmer and later translated into English. A thematic analysis was undertaken, with medical abortion experiences coded according to the Cambodia comprehensive abortion care protocol. Results We interviewed 16 women and 13 providers between August and November 2018. Most women reported being married and had at least one child. Among factory workers the major reported reasons for abortion were birth spacing and financial constraints. Family, friends, or co-workers were the major information resources regarding abortion and contraception, and their positive or negative experiences strongly influenced women's attitude towards both. Medical abortion pills were not always provided with adequate instructions. Half of the participants had a manual vacuum aspiration procedure performed after medical abortion. While women knew the side effects of medical abortion, many did not know the adverse warning signs and the signs of abortion completion. Only three women started post abortion family planning, as most of the women expressed fear and hesitation due to concerns about side effects of modern contraception. Fear of infertility was particularly reported among young women without children. Conclusion This research shows that in this setting not all women are receiving comprehensive abortion care and contraceptive counselling. Provision of accurate and adequate information about abortion methods and modern contraception was the dominant shortfall in abortion care. Future work to address this gap could involve the development of appropriate interventions and informative tools for women in the Cambodian garment industry such as through existing client contact-centres or social media, including creation of videos or posts on topics that come from clients questions.